Charleston - French Hugenot Church - Hugh C. Leighton Co.... (Wikimedia Commons, 1912)
Notice image issue de Wikimedia Commons. Titre: Charleston - French Hugenot Church. Photomechanical print (postcard): halftone, tinted Divided back No. 26345 Made in Germany
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale; église; Carte postale